Вимушена міграція та її вплив на ринок праці в Україні - Комарницька, Г. О.; Komarnytska, H. O.; Ястремська, Н. М.; Yastremska, N. M.; Павленко, Н. В.; Pavlenko, N. V.; Павленко Наталія Вікторівна (Наукові перспективи. - 2022. - № 6(24). - С. 306-319, 2022)
Вивчено тенденції вимушеної міграції в Україні в регіональному контексті крізь призму аналізу їх впливу на ситуацію на вітчизняному ринку праці. Досліджено статистику вимушеної міграції внаслідок збройної агресії держави-окупанта. Наведено класифікацію населених пунктів у країні, яка знаходиться в стані війни. Вивчено кількість населення до початку війни і після міграційної хвилі. Проаналізовано проблему вимушеної міграції, пов’язану із диспропорціями у рівні оплати праці та кількості робочих місць на ринку праці у регіонах походження та регіонах переміщення громадян. Досліджено кількість вакансій у регіональних центрах зайнятості та рівень безробіття у регіонах, куди прибуло найбільше вимушених мігрантів. Наведено основні проблеми на ринку праці України в умовах війни та окреслено шляхи їх вирішення. Встановлено перспективи зміни попиту на спеціалістів на ринку праці у поточних умовах.

Forced migration is an uncontrollable phenomenon, as often in conditions of danger to life and health a person is not able to fully assess the direction of its movement and the opportunity to fully organize their lives in a new place. Ukraine first encountered the notion of forced migration in 2014 due to the annexation of the Autonomous Republic of Crimea and the military-political conflict in the east of the country. However, in this case the situation was quickly brought under control. The events of the last few months have caused a multimillion-dollar wave of forced migrants to settle chaotically in northern, central and western Ukraine. In such conditions, a critical impact on the entire economic, social, medical and educational spheres is natural. One of the biggest challenges is its impact on the abor market in Ukraine, as a source of financial resources for citizens to ensure their livelihoods. Thus, the scientific article examines the scale of forced migration in 2014 and the key problems that accompanied it. A comparative characterization of forced and voluntary migration is carried out. The statistics of forced migration due to the armed aggression of the occupying power are studied. The classification of settlements in a country at war is given. The population before the war and after the migration wave was studied. The level of savings of citizens at the time of the war has been established. The problem of forced migration related to disparities in the level of wages and the number of jobs in the labor market in the regions of origin and regions of movement of citizens is analyzed. For these purposes, the average salary in such regions for 2019-2021 is analyzed. The number of vacancies in regionalemployment centers and the unemployment rate in the regions with the largest number of forced migrants were studied. The main problems in the labor market of Ukraine during the war are presented and ways to solve them are outlined. Prospects for changing the demand for specialists in the labor market in the current conditions have been established.

Изучены тенденции вынужденной миграции в Украине в региональном контексте через призму анализа их влияния на ситуацию на отечественном рынке труда. Исследована статистика вынужденной миграции в результате вооруженной агрессии государства-оккупанта. Приведена классификация населенных пунктов в стране, которая находится в состоянии войны. Изучено количество населения до начала войны и после миграционной волны. Проанализирована проблема вынужденной миграции, связанная с диспропорциями в уровне оплаты труда и количества рабочих мест на рынке труда в регионах происхождения и регионах перемещения граждан. Исследовано количество вакансий в региональных центрах занятости и уровень безработицы в регионах, куда прибыло больше всего вынужденных мигрантов. Приведены основные проблемы на рынке труда Украины в условиях войны и определены пути их решения. Установлены перспективы изменения спроса специалистов на рынке труда в текущих условиях.
Forced migration and its impact on the labor market in Ukraine
Keywords: Економічні науки. Економічна безпека. Economics. Economic Security. Экономические науки. Экономическая безопасность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; ринок праці; labor market; рынок труда; внутрішньо переміщені особи; internally displaced persons; внутренне перемещенные лица; вимушена міграція; forced migration; вынужденная миграция; рівень безробіття; unemployment rate; уровень безработицы; середня заробітна плата; average salary; средняя заработная плата; вакансії; vacancies; вакансии